1998
DOI: 10.3109/09637489809086409
|View full text |Cite
|
Sign up to set email alerts
|

Food aversions in eating disorders

Abstract: The food aversions of a group of anorexia nervosa patients, bulimia nervosa patients, and no eating disordered individuals (controls) were compared. An open questionnaire was used to obtain data on the eating aversions of each of the three populations. The foodstuffs were placed in categories according to their nutritional value. They were also converted into nutrients, and the average value for each population was calculated. With the exception of the 'legumes' and 'dry fruits' categories, the degree of avers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…28,29 CFA develops in patients receiving gastrointestinally toxic chemotherapy 30,31 and a clear association between anorexia and food aversion has been demonstrated in cancer patients 7 and in women affected by anorexia nervosa. 32,33 In the present study, it is noteworthy that all patients with food aversions reported that they avoided meat, especially red meat. This is in accordance with the study of Dobell et al that, comparing the food preferences of patients undergoing maintenance hemodialysis and continuous ambulatory peritoneal dialysis with those of age-and sex-matched controls, found that red meat was the most unpopular food group for all dialysis patients.…”
Section: Discussionmentioning
confidence: 92%
“…28,29 CFA develops in patients receiving gastrointestinally toxic chemotherapy 30,31 and a clear association between anorexia and food aversion has been demonstrated in cancer patients 7 and in women affected by anorexia nervosa. 32,33 In the present study, it is noteworthy that all patients with food aversions reported that they avoided meat, especially red meat. This is in accordance with the study of Dobell et al that, comparing the food preferences of patients undergoing maintenance hemodialysis and continuous ambulatory peritoneal dialysis with those of age-and sex-matched controls, found that red meat was the most unpopular food group for all dialysis patients.…”
Section: Discussionmentioning
confidence: 92%
“…These two QADS subscales refer to core disgust in its basic meaning, namely, to the rejection of inedible food (Rozin, Haidt, & McCauley, 2000). Whereas in eating disorders, pathological disgust towards food and food aversions are common (e.g., Harvey et al, 2002; Vaz, Alcaina, & Guisado, 1998), to our knowledge, no studies exist concerning food aversions in schizophrenia. However, Folley and Park (2010) observed decreased positive ratings for food with increasing anhedonia in schizophrenic patients.…”
Section: Discussionmentioning
confidence: 98%
“…We reported that both AN and recAN participants consumed significantly less cholesterol than HCs. This is unsurprising as people with AN tend to avoid foods that are high in cholesterol such as dairy products and meats [7,64]. Research on the lipid profile of AN patients has shown that they often exhibit hypercholesterolaemia [65,66].…”
Section: Nutrient Intakementioning
confidence: 99%